Global classroom with Lancaster University: Keys to mastering job interviews - Nur Anisnabila, Dianah; Wan Noor Farah, Wan Shamsuddin; Siti Asma’, Yaacob (Centre for Modern Languages, 2024)
Paya Besar, 9 May 2024 - "Preparation is the key to success in job interviews," emphasised Ms. Nur Sabrina Zafiran, a PhD candidate in Linguistics from Lancaster University, United Kingdom, during the Global Classroom session last month. This event held particular significance for the students enrolled in UHL2432 English for Professional Communication, who were scheduled to undergo mock job interview assessments the following week.